2020
DOI: 10.1002/fsn3.2044
|View full text |Cite
|
Sign up to set email alerts
|

Safety of high‐dose Puerariae Lobatae Radix in adolescent rats based on metabolomics

Abstract: Puerariae Lobatae Radix (PLR) is the dried root of the leguminous plant Pueraria lobata and is a common component of health products and medicines. Although it is considered safe, some studies have reported that PLR has hepatotoxicity and estrogen‐like effects. In this study, the safety of high doses of PLR water extract administered to adolescent SD rats for 30 days was evaluated by biochemical, histopathological, and metabolomic analyses. Overall, there were no significant differences between the low‐dose an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…PLR is also a medicine and food homologous herb that is widely used to treat gastrointestinal and cardiovascular diseases [ 18 , 19 , 20 ]. Notably, a recent study has confirmed the safety of PLR by feeding high doses of aqueous PLR extract to rats [ 21 ]. Therefore, it is reasonable to test PLR in the treatment of PE.…”
Section: Introductionmentioning
confidence: 99%
“…PLR is also a medicine and food homologous herb that is widely used to treat gastrointestinal and cardiovascular diseases [ 18 , 19 , 20 ]. Notably, a recent study has confirmed the safety of PLR by feeding high doses of aqueous PLR extract to rats [ 21 ]. Therefore, it is reasonable to test PLR in the treatment of PE.…”
Section: Introductionmentioning
confidence: 99%
“…And it can amplify small differences in upstream gene and protein expression, and further in‐depth analysis of the metabolic pathways related to different metabolites can explain the mechanism of action of the research object (Wu et al., 2021 ). This technology has been widely used in food science (Chen et al., 2020 ), medicine (Wang, Zhang, et al., 2020 ; Wang, Chen, et al., 2020 ; Wang, Gong, et al., 2020 ; Wang, Jia, et al., 2020 ) and other fields. Nontargeted metabolomics can comprehensively and unbiasedly reflect the metabolic state of small molecules in organisms, which is conducive to the screening of biomarkers and the construction of dynamic metabolic networks in organisms (Wang, Zhang, et al., 2020 ; Wang, Chen, et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomics is a technique to study the metabolites and their dynamic changes before and after being stimulated or disturbed for the biological system (e.g., after a specific gene variation or environmental change). Metabolomics has been widely used in plant molecular phenotype (Showkat et al., 2019 ), drug safety (Chen et al., 2021 ; Yu et al., 2018 ), molecular pathology (Yang & Lao, 2019 ), mechanism of drug action (Su et al., 2020 ), and disease diagnosis (Karakioulaki & Stolz, 2019 ). In addition, it was also used to evaluate the impact of storage environment on food quality (Guo et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%